Modeling Macro-Critical Energy Sectors in Low-Income Countries : A General Framework and an Application to Cote d'Ivoire - Fabig, Holger (Washington, D.C. : International Monetary Fund, 2008)
This paper proposes a general framework for monitoring macro-critical energy sectors in low-income countries, defined as consisting of the three subsectors of crude oil and natural gas production, refinery, and electricity production. It aims to derive consistent information on physical and financial flows in the sector, including on interlinkages between the subsectors. It then applies this framework to Cote d'Ivoire. While being an important source of growth, the Ivoirien energy sector is found to have important shortcomings, in particular as regards transparency, efficiency and contribution to fiscal revenue. Among the key problems are partially intransparent production sharing arrangements for hydrocarbon production, price distortions for natural gas, administered prices for refined petroleum products, underfunding and lack of investment in the electricity sector, and inefficient government subsidies in the latter two subsectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet